Calcium-chelating peptides from rabbit bone collagen:characterization, identif ication and mechanism elucidation - Fuhuan Yuan; Yu Fu; Liang Ma; Hankun Zhu; Yong Yu; Xin Feng; Yi Sun; Hongjie Dai; Xin Liu; Zhengfang Liu; Yuhao Zhang (Food Science and Human Wellness)
This study aimed to characterize and identify calcium-chelating peptides from rabbit bone collagen and explore the underlying chelating mechanism. Collagen peptides and calcium were extracted from rabbit bone by instant ejection steam explosion (ICSE) combined with enzymatic hydrolysis, followed by chelation reaction to prepare rabbit bone peptide-calcium chelate (RBCP-Ca). The chelating sites were further analyzed by liquid chromatography-tandem mass (LC-MS/MS) spectrometry while the chelating mechanism and binding modes were investigated. The structural characterization revealed that RBCP successfully chelated with calcium ions. Furthermore, LC-MS/MS analysis indicated that the binding sites included both acidic amino acids (Asp and Glu) and basic amino acids (Lys and Arg). Interestingly, three binding modes, namely Inter-Linking, Loop-Linking and Mono-Linking were for the first time found, while Inter-Linking mode accounted for the highest proportion (75.1%), suggesting that chelation of calcium ions frequently occurred between two peptides. Overall, this study provides a theoretical basis for the elucidation of chelation mechanism of calcium-chelating peptides.